Explaining surface interactions for common associated gangues of rare earth minerals in response to the oxalic acid - Saeed Chehreh Chelgani; Brian Hart (International Journal of Mining Science and Technology, 2018)
In the flotation of rare earth minerals (REMs), oxalic acid is reportedly acting both as a depressant and pH modifier. Although results of testing have established the significance of oxalic acid in the flotation process, its specific role in either the recovery or selectivity of REMs over their common gangue minerals is not well understood. Pulp pH reduction trials with alternative acids have not shown the same effect on the REMs recovery or the depression of gangue phases. This work studies the effect of oxalic acid on the surface of common REMs gangue minerals (quartz and carbonates (dolomite and calcite)) in a series of conditioning tests. Gangue surface analyses by time of flight secondary ion mass spectroscopy (TOF-SIMS) indicate that oxalic acid inhibits the transfer of secondary ions generated during the conditioning process from one mineral to another. In this regard, the oxalate anion acts to fix ions in solution through chelation, limiting their participation in surface adsorption. Keywords: Oxalic acid, Rare earth, Silicate, Carbonate, TOF-SIMS